1998
DOI: 10.1088/0953-8984/10/46/003
|View full text |Cite
|
Sign up to set email alerts
|

Fermiology of Cr and Mo

Abstract: An interpretation of the two-dimensional angular correlation of positron annihilation radiation (2D-ACAR) for paramagnetic chromium (Cr) and molybdenum (Mo) is presented. Rather than explaining the significant differences in the resulting k-space occupancies in terms of different Fermi surface (FS) topologies, the recovery of a FS topology for paramagnetic Cr in agreement with band theory (and similar to the Mo experiment) through the application of a recently introduced maximum-entropy-based filtering techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…Also it has to be considered the application of the LCW-theorem is only valid if the positron wave function can be characterized as a plane wave, which is not true if strong correlation effects are present, like it is the case for Cr [14]. To summarize, we were able to reproduce the results from previous measurements [8] we also could show, that the 2D-ACAR spectrum is drastically different in the anti-ferromagnetic and in the paramagnetic phase. However, the interpretation of our data with respect to the calculation remains an unsolved challenge.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Also it has to be considered the application of the LCW-theorem is only valid if the positron wave function can be characterized as a plane wave, which is not true if strong correlation effects are present, like it is the case for Cr [14]. To summarize, we were able to reproduce the results from previous measurements [8] we also could show, that the 2D-ACAR spectrum is drastically different in the anti-ferromagnetic and in the paramagnetic phase. However, the interpretation of our data with respect to the calculation remains an unsolved challenge.…”
Section: Discussionsupporting
confidence: 57%
“…Generally, the agreement of our measurement with previous 2D-ACAR measurements (see ref. [8]) on paramagnetic Cr is considerable. However, the discrepancies between our data and the SPRKKR calculations are quite substantial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 The first three-dimensional reconstruction of the momentum density and Fermi surface in Cr was by Kubota et al, 55 followed a few years later by Fretwell et al who emphasized the advantages for deconvoluting the measured spectra prior to reconstruction. 56,57 One of the particularly perplexing issues was that the comparison of the experimental Cr spectra with theory, for both the positron annihilation measurements 58 and later Compton scattering, 59,60 was always substantially less favorable than the comparison between measurement and theory in Sec. V. Positron measurements in Mo, which being isoelectronic to Cr was thought to possess a very similar Fermi surface, conversely agreed very well with theoretical predictions.…”
Section: The Spin-density Wave Of Crmentioning
confidence: 99%
“…V. Positron measurements in Mo, which being isoelectronic to Cr was thought to possess a very similar Fermi surface, conversely agreed very well with theoretical predictions. 58 The eventual explanation for this came much more recently, when Laverock et al showed that the discrepancy came from a combination of inadequacies in the description of the electron-positron interaction (the socalled enhancement) and a real difference in the band structure. 4 Laverock et al were also able to show (Fig.…”
Section: The Spin-density Wave Of Crmentioning
confidence: 99%